2008
DOI: 10.1371/journal.pone.0002080
|View full text |Cite
|
Sign up to set email alerts
|

SalK/SalR, a Two-Component Signal Transduction System, Is Essential for Full Virulence of Highly Invasive Streptococcus suis Serotype 2

Abstract: Background Streptococcus suis serotype 2 (S. suis 2, SS2) has evolved into a highly infectious entity, which caused the two recent large-scale outbreaks of human SS2 epidemic in China, and is characterized by a toxic shock-like syndrome. However, the molecular pathogenesis of this new emerging pathogen is still poorly understood.Methodology/Principal Findings89K is a newly predicted pathogenicity island (PAI) which is specific to Chinese epidemic strains isolated from these two SS2 outbreaks. Further bioinform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
126
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 121 publications
(134 citation statements)
references
References 63 publications
4
126
2
2
Order By: Relevance
“…2008; Li et al. 2008). As we performed before (Feng and Cronan 2009, 2010), RNA integrity/quality was validated by separation of 1.0% agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…2008; Li et al. 2008). As we performed before (Feng and Cronan 2009, 2010), RNA integrity/quality was validated by separation of 1.0% agarose gel electrophoresis.…”
Section: Methodsmentioning
confidence: 99%
“…Research on gene regulation has focused mainly on protein regulators such as two-component or stand-alone regulators, including LuxS , CcpA , CovR ), CiaR/H , Ihk/Irr (Han et al 2012), AdcR (Aranda et al 2009b), ArgR , SalK/R (Li et al 2008), RevSC21 ), and Rgg . Recent studies, however, have revealed that regulatory RNAs (small RNAs from intergenic regions [sRNAs] and antisense RNA [asRNA]) have emerged as key regulators of virulence in several bacteria (Romby et al 2006;ToledoArana et al 2009;Waters and Storz 2009;Sharma et al 2010;Wurtzel et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (22) showed that the SalKR mutant strain had no pathogenicity in the piglet infection experiment. On the contrary, functional complementation of salKR into the isogenic salKR mutant strain restored its high pathogenicity.…”
Section: Salk/salrmentioning
confidence: 99%